LinkedSV for detection of mosaic structural variants from linked-read exome and genome sequencing data - Li Fang (Nature Portfolio, 2019)
Compared to single nucleotide variants and short indels, structural variants (SVs) are often more challenging to detect using high-throughput sequencing based methods. Here, the authors develop LinkedSV, a computational tool for SV detection using linked-read exome and genome sequencing data.